Comparing the Effect of Non-nutritive Sucking and Abdominal Massage on Feeding Tolerance in Preterm Newborns - Saideh Marzieh Fazli; Ashraf Mohamadzadeh; Maryam Salari; Soheila Karbandi (Journal of Evidence-Based Care, 2017)
Background:Enteral feeding intolerance is a major problem in the preterm neonates. Non-nutritive sucking and abdominal massage are among the most important nutritional interventions in this regard. Aim: This study aimed to compare the effect of non-nutritive sucking and abdominal massage on feeding tolerance in the preterm newborns. Method: This clinical trial was conducted on 52 preterm neonates in the Neonatal Intensive Care Unit of Imam Reza Hospital in Mashhad, Iran. The subjects were randomly divided into three groups, namely abdominal massage (17 newborns), non-nutritive sucking (18 newborns), and control groups (17 newborns). In the abdominal massage group, the intervention was fulfilled for 15 min twice a day, and in the non-nutritive sucking group, the intervention was performed for 10 min three times a day within 7 days. The control group only received tube feeding every two h without any intervention. Feeding tolerance was examined in terms of gastric residuals, vomiting, and abdominal distention. The data were collected through the recording daily information form. The data were analyzed through SPSS version 23, using ANOVA test and marginal models. Results: The mean gestational age of the abdominal massage group was 32.8±1.0 weeks. This value was 32.5±1.3 weeks in both sucking and control groups. Generalized estimating equation revealed that non-nutritive sucking was effective in the absence of distention (P=0.01) and vomiting (P=0.01). However, abdominal massage was effective only in the absence of vomiting (P=0.01). Implications for Practice: The use of non-nutritive sucking can increase the feeding tolerance in the preterm newborns.